Type of dietary fat intakes in relation to all-cause and cause-specific mortality in US adults: an iso-energetic substitution analysis from the American National Health and Nutrition Examination Survey linked to the US mortality registry. Issue 4 (2nd March 2018) - Ricci, Cristian; Baumgartner, Jeannine; Zec, Manja; Kruger, Herculina Salome; Smuts, Cornelius M.
Abstract: Accumulating evidence indicates that saturated fat intake is related to mortality risk increase, whereas unsaturated fat intake is associated with reduced mortality risk. The aim of the present study was to estimate the mortality risk reduction related to a dietary change from saturated fat to mono- or polyunsaturated fat intake. The American National Health and Nutrition Examination Surveys conducted between 1999 and 2010 were linked to the 2011 national US death registry resulting in an observational prospective mortality study. Proportional hazards Cox models were used to evaluate the association between saturated, monounsaturated and polyunsaturated fat with all-cause and cause-specific mortality. Substitution analysis was conducted to estimate an iso-energetic substitution of 10 % of the energy from dietary fat intake applied to the substitution of saturated fat with an equal amount of energy from monounsaturated or polyunsaturated fat. The highest tertile intakes of saturated fat resulted in an increased risk (12 %) of all-cause and specific-cause mortality, whereas the highest tertile intakes of polyunsaturated fat resulted in a reduced risk (7 %) of all-cause and specific-cause mortality when compared with the corresponding lowest tertile. Iso-energetic substitution revealed that a substitution of 10 % of energy (from total fat) from saturated fat to an equal amount of energy from monounsaturated or polyunsaturated fat resulted in a significant reduction of the mortality risk ranging from 4 to 8 %. Iso-energetic substitution of saturated fat with monounsaturated and polyunsaturated fat reduced all-cause and specific-cause mortality in US adults.